Management of Acute Abdomen: Evidence-Based Approaches, Diagnostic Challenges, and Surgical Innovations - saroj, Jitendra kumar; Bhatnagar, Abhay; Yadav, Ganesh Chandra (Journal of Neonatal Surgery, 2024)
Acute abdomen is an acute and severe pain in the abdomen that is a sign of underlying intra-abdominal pathology that may necessitate urgent or emergent action. It is characterised by a wide range of causes of obstructive, inflammatory, vascular and perforative etiologies, which demand different diagnoses and treatment efforts. Nonspecific symptoms augment the difficulty of timely diagnosis, particularly in elderly, immunocompromised and pregnant patients. Even though diagnostic instruments such as computed tomography (CT) and magnetic resonance imaging (MRI) have improved the precision of diagnosis, resource constraints in low- and middle-income countries (LMICs) continue to increase the delays and poorer outcomes. Diagnostic imaging overuse has led to an increase in healthcare expenditure and unnecessary radiation exposure in high-income countries. The development of surgical procedures, especially minimally invasive surgery such as laparoscopy and robotic surgery, has minimised recovery time and pain after surgery. Moreover, there are also Enhanced Recovery After Surgery (ERAS) protocols that have played a significant role in the improvement of the postoperative outcomes through the encouragement of early mobility, pain management and nutrition. This is a review of evidence-based practices in the diagnosis and treatment of acute abdomen, and it discusses the issues in diagnosis, management paradigms, and the importance of surgical innovations. There is a focus on the incorporation of new technologies and optimization of clinical pathways to enhance patient outcomes in the world.